Dialogical Interaction in Indonesian Language Learning: An Ethnographic Study of Teacher Strategies and Student Engagement in a Junior High School in Lumajang - Ary Fawzi; Imam Suyitno; Sainee Tamphu (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
There has been research on learning interaction, there is still a gap in understanding how communication patterns, pedagogical strategies, and student responses in Indonesian language learning. Based on this, this study aims to analyze interaction patterns, teacher strategies in managing interactions, and student responses to methods in learning. This research used a classroom ethnography approach. Data were collected through participatory observation, in-depth interviews, and document analysis at three state junior high schools (SMPN) in Lumajang. This research ensures data validity through triangulation of techniques and sources. This research analyzes data interactively with the stages of data reduction, data presentation, and conclusion making. The research findings show that there are four categories of interaction patterns in Indonesian language learning, namely task-oriented interaction, discussion-based interaction, evaluation-based interaction, and post-evaluation reflective interaction. Teachers' pedagogical strategies-such as building emotional closeness, utilizing learning technology, and applying differentiation and scaffolding-are proven to be able to increase students' involvement in the learning process. In addition, students showed positive responses to interactive activities, peer evaluation and learning reflection. The findings of this study confirm the importance of developing teachers' pedagogical competence and innovating learning strategies to create a more interactive, participatory and inclusive learning environment in the context of Indonesian language learning in junior secondary schools.